Seismicity of the repeating earthquake clusters in the northern Xiaojiang fault zone and its implications - Zhou, Yun; Xu, Lisheng; Wu, Jianping; Li, Chunlai; Fang, Lihua; Pan, Zhengyang (Frontiers in Earth Science, 2022)
The Xiaojiang fault zone (XJF) located at the southeastern margin of the Tibetan plateau was frequently struck by destructive earthquakes throughout history. Some studies showed that repeating earthquakes may be used to estimate fault slip rates, and even to monitor the pre-slip prior to large asperity. This study focuses on the repeating earthquakes recorded by a high-density seismic array in northern section of the XJF, a segment ruptured by the 1733 Dongchuan M7.8 earthquake. Using the waveform cross-correlation and relocation techniques, we processed the continuous seismic recordings from seismic stations of the array, and confirmed 27 clusters of repeating earthquakes. The repeaters are located in three relatively independent sub-areas, the areas A, B and C. Area A is close to the source areas of 2014 Ludian Ms6.5 and the 2020 Qiaojia Ms5.0 earthquakes; by analyzing the recurrence intervals of repeating clusters, we found that Ludian earthquake had an insignificant triggering effect on surrounding events, while the triggering effect from Qiaojia earthquake was obvious. The clusters in area B were located very close to the most northern tip of the XJF, which should be associated with an asperity preparing for a large earthquake on the northern XJF. Together with a repeating cluster identified in a previous study and the seismicity pattern revealed by our seismic array, we determine the geometry of the asperity and slip rate, and further helps to estimate a potential Mw7.1 earthquake for the asperity, where no M>7 earthquakes have occurred since the 1733 Dongchuan M7.8 earthquake. The clusters in area C are more like human-induced earthquakes because they are concentrated during the daytime when local people are at work, and thus they can not be used for the study of tectonic deformation. This study clearly indicates that the repeating earthquakes can be triggered by the moderate earthquake nearby, and also indicates that repeating earthquakes can be used to estimate fault slip rates and to outline locked asperities.